2016
DOI: 10.1111/1556-4029.13081
|View full text |Cite
|
Sign up to set email alerts
|

Ancestry Estimation in Forensic Anthropology: Geometric Morphometric versus Standard and Nonstandard Interlandmark Distances

Abstract: Standard cranial measurements are commonly used for ancestry estimation; however, 3D digitizers have made cranial landmark data collection and geometric morphometric (GM) analyses more popular within forensic anthropology. Yet there has been little focus on which data type works best. The goal of the present research is to test the discrimination ability of standard and nonstandard craniometric measurements and data derived from GM analysis. A total of 31 cranial landmarks were used to generate 465 interlandma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 47 publications
1
17
1
Order By: Relevance
“…An obvious disadvantage of these methods is the lack of a reference sample for every population which would inevitably result in erroneous classifications of target individuals not represented in the databases. This is supported by several validation studies [13][14][15].…”
Section: Introductionsupporting
confidence: 66%
“…An obvious disadvantage of these methods is the lack of a reference sample for every population which would inevitably result in erroneous classifications of target individuals not represented in the databases. This is supported by several validation studies [13][14][15].…”
Section: Introductionsupporting
confidence: 66%
“…The use of non-standard methodological approaches enables us to explore the range and pattern of human variation from a different angle and ultimately may lead to the development of innovative osteometric techniques. The benefit of this approach is illustrated by recent work which showed that integrating non-standard measurements provides more information for complex population structures where there is a high rate of immigration, migration and relaxed border controls [43]. Additionally, virtual models derived from clinical CT data enable us to develop new forensic anthropological techniques that are not based on biased skeletal databases.…”
Section: Application To Forensic Anthropologymentioning
confidence: 99%
“…Another study used GM to assist in distinguishing between Hispanics and American blacks and whites, an ancestry estimation that has previously been difficult to perform accurately with traditional craniometrics (38). Geometric morphometric analysis has not yet been shown to be more accurate than traditional linear measurement methods, but these types of methods are still being refined (59,60).…”
Section: Invited Reviewmentioning
confidence: 99%
“…The three-dimensional nature of GM data in its original state allows for the study of shape without size influences, which can incorporate sophisticated statistics into the formation of biological profiles. While GM can be used to test a variety of hypotheses (46,47), several methods have been developed in recent years to estimate sex and ancestry from cranial, dental, and postcranial information with varying degrees of success (38,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). The most holistic of these methods is 3D-ID, a computer program that acts in much the same way as Fordisc to produce sex and ancestry estimates of an unknown cranium (54).…”
Section: Invited Reviewmentioning
confidence: 99%